The antioxidant potential of copper oxide nanoparticles synthesized from a new bacterial strain - HASAN GHALI ABDULHASAN ALSHAMI; WIJDAN H. AL-TAMIMI; RASHID RAHIM HATEET (Society for Indonesian Biodiversity, 2023)
Abstract. Alshami HGA, Al-Tamimi WH, Hateet RR. 2023. The antioxidant potential of copper oxide nanoparticles synthesized from a new bacterial strain. Biodiversitas 24: 2666-2673. Copper oxide nanoparticles (CuONPs) have recently gained much attention due to their potential in various fields. The present study aimed to screen nine bacterial strains (Klebsiella quasipneumoniae KP18-31, K. pneumoniae IOB-L, K. quasipneumoniae subsp. similipneumoniae 2437, Bacillus cereus DBA1, B. thuringiensis MSP51, Neobacillus drentensis ROA042, Enterococcus faecalis 2674, Exiguobacterium mexicanum AB201, and Acinetobacter lwoffii K34) isolated from produced water of oil field reservoirs for their ability to biosynthesize CuONPs, as well as characterize and evaluate the antioxidant potential of the manufactured CuONPs. Biosynthesized CuONPs were characterized using XRD, TEM, AFM, and zeta potential analysis. In addition, the DPPH method was used to analyze the antioxidant activity of CuONPs. The results revealed that five of the nine isolates could synthesize CuONPs. B. thuringiensis MSP5 was the best and most productive among them, and it was used for the first time in this present study as an oil field bacteria for the biosynthesis of CuONPs. The results showed that CuONPs have a spherical shape with an average size of 20, 33, and 75 nm based on XRD, TEM, and AFM analysis, respectively. The zeta potential value of the synthesized CuONPs was -12.4 mV. The antioxidant results demonstrated that CuONPs have a remarkable scavenging activity with an IC50 value of 141.68 ?g/mL. This study concluded that CuONPs were excellent free radical scavengers.